2017
DOI: 10.14687/jhs.v14i2.4397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of marbling art therapy activities on the anxiety levels of psychiatric patients

Abstract: Purpose: Study was conducted to explore the impact of marbling art therapy on the anxiety levels of patients with schizophrenia and bipolar disorder. Methods: Data for the study were at a university hospital and in the psychiatric service,polyclinic of a State Hospital with 34 patients diagnosed with schizophrenia and 34 patients diagnosed with bipolar disorder. Investigations were carried out with study groups and a control group. Findings:Following marbling, it was found that there were significant decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…In the present study, the intervention group's mean depression and anxiety scores decreased, but no statistically significant change was observed in the intervention group, which indicates that group activities reduce anxiety and depression levels. Studies have shown that art therapy reduce individuals' aggression, anxiety, stress and depression levels 43,44 . No study was found to be conducted with a population similar to that of the present study; however, after patients with cancer participated in art therapy, their depression, anxiety and stress levels decreased and their satisfaction with life and coping behaviors changed in a positive direction 45,46 …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the present study, the intervention group's mean depression and anxiety scores decreased, but no statistically significant change was observed in the intervention group, which indicates that group activities reduce anxiety and depression levels. Studies have shown that art therapy reduce individuals' aggression, anxiety, stress and depression levels 43,44 . No study was found to be conducted with a population similar to that of the present study; however, after patients with cancer participated in art therapy, their depression, anxiety and stress levels decreased and their satisfaction with life and coping behaviors changed in a positive direction 45,46 …”
Section: Discussionmentioning
confidence: 57%
“…Studies have shown that art therapy reduce individuals' aggression, anxiety, stress and depression levels. 43,44 No study was found to be conducted with a population similar to that of the present study; however, after patients with cancer participated in art therapy, their depression, anxiety and stress levels decreased and their satisfaction with life and coping behaviors changed in a positive direction. 45,46 Shella 47 | 347 with these difficulties.…”
Section: Discussionmentioning
confidence: 66%
“…Penelitian tersebut menghasilkan bahwa ada kemungkinan jika art therapy efektif untuk menjadi intervensi untuk kecemasan pada individu dewasa karena dapat meningkatkan regulasi stres, regulasi kognitif, dan regulasi emosi. Lebih lanjut lagi dijelaskan bahwa art therapy dan proses kreatif memberikan kesempatan pada individu untuk mengekspresikan dirinya dan meningkatkan self-awarnes (Akhan & Atasoy, 2017).…”
Section: Pendahuluanunclassified
“…Meskipun begitu, efek terapeutik yang dihasilkan art therapy, tentu akan lebih berdampak ketika dipasangkan dengan terapi lain yang lebih efektif dalam menangani kecemasan. Mengingat art atau seni sendiri disimbolkan sebagai stimulus berbagai aspek dari emosi yang dimiliki individu dan menyediakan insight secara mendalam pada pemahaman diri (Akhan & Atasoy, 2017). Lebih lanjut dijelaskan bahwa, pada proses art therapy, dibandingkan melihat pada konten kesadaran, individu ditolong untuk merubah emosi menjadi ekspresi dalam bentuk konkrit melalui penggunaan kertas, musik, menari (dancing), dan berbagai aktivitas seni lainnya (Blatnet, dalam Akhan & Atasoy, 2017).…”
Section: Pembahasanunclassified